TESS in the Solar System. (12th October 2018) - Pál, András; Molnár, László; Kiss, Csaba
Abstract: The Transiting Exoplanet Survey Satellite ( TESS ), launched successfully on 2018 April 18 will observe nearly the full sky, and will provide timeseries imaging data in ∼27-day-long campaigns. TESS is equipped with four cameras, each of which has a field of view of 24 × 24°. During the first two years of the primary mission, one of these cameras, Camera #1, is going to observe fields centered at an ecliptic latitude of 18°. While the ecliptic plane itself is not covered during the primary mission, the characteristic scale height of the main asteroid belt and Kuiper Belt implies that a significant amount of small solar system bodies will cross this camera's field of view. Based on the comparison of the expected amount of information of TESS and Kepler /K2, we can compute the cumulative étendues of the two optical setups. This comparison results in roughly comparable optical étendues; however, the net étendue is significantly larger in the case of TESS because all of the imaging data provided by the 30-minute cadence frames are downlinked rather than the pre-selected stamps of Kepler /K2. In addition, many principles of the data acquisition and optical setup are clearly different, including the level of confusing background sources; full-frame integration and cadence; the field-of-view centroid with respect to the apparent position of the Sun; as well as the differences in the duration of the campaigns. As one would expect, TESS will yield timeseries photometry, and hence rotational properties for only brighter objects, but in terms of spatial and phase space coverage, this sample will be more homogeneous and more complete. Here, we review the main analogs and differences between the Kepler /K2 mission and the TESS mission, focusing on scientific implications and possible yields related to our solar system.